Fabrication and Characterization of Manganite Based p–n Junction. (2018) - Rajyaguru, Bhargav; Boricha, Hetal; Shrimali, V.G.; Joshi, A.D.; Asokan, K.; Shah, N.A.; Solanki, P.S.
Abstract: In this communication, we report the process to fabricate high quality LaMnO3 / La0.7 Ca0.3 MnO3 / LaAlO3 heterostructure consists of oxygen deficient n–type semiconducting LaMnO3–δ 50nm layer attached with p–type La0.7 Ca0.3 MnO3 100nm manganite layer. Heterostructure was grown using easy, simple, vacuum free, cost effective and environmentally friendly chemical solution deposition (CSD) method. Manganite based p–n junction was characterized by current–voltage (I–V) characteristics and electric field dependent junction resistance measurements at different temperatures. I–V curves have been understood for the charge transport mechanisms across the junction in the context of thermionic emission mechanism while complex electroresistance (ER) behavior has been discussed on the basis of role of depletion region and charge injection processes across the junction.